Hereditary angioedema: Linking complement regulation to the coagulation system. Issue 1 (16th December 2018) - Levi, Marcel; Cohn, Danny M.; Zeerleder, Sacha
Abstract: Congenital deficiency of C1 inhibitor, the main inhibitor of the classic complement system pathway, leads to paroxysmal angioedema (hereditary angioedema) that can be debilitating or life‐threatening for affected patients. In the past few years many new insights on the pathogenesis of angioedema formation in the presence of low levels of C1 inhibitor has been accumulated. There is a central role for bradykinin that is released upon activation of the kallikrein‐kinin system that is insufficiently controlled by adequate levels of C1 inhibitor. As C1 inhibitor also possesses a central regulatory role of other plasma systems, including the contact activation system of coagulation and the plasminogen‐plasmin system that governs endogenous fibrinolysis, it is interesting to observe the effects of C1 inhibitor deficiency on activation of these systems and relevance for hemostasis in vivo and thrombo‐embolic disease. Interestingly, and despite significant activation of these pathways, C1 inhibitor deficiency is not at all associated with a hemorrhagic tendency or prothrombotic state. New therapeutic options for treatment of C1 inhibitor efficiency have become available in recent years, including various forms of C1 inhibitor concentrate. Restoration of C1 inhibitor levels in patients with hereditary angioedema has not resulted in thrombotic complications or any other relevant disorder associated with the hemostatic system.